A comparison of mathematical tasks types used in Indonesian and Australian textbooks based on geometry contents - Hidayah, Miftahul; Forgasz, Helen (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
This study examined the type of mathematical tasks in two Australian and two Indonesian mathematics textbooks for 7th-grade students. The quantitative data were collected from the coding results of the tasks in the textbooks. The tasks were coded based on six categories: the presentation forms, the cognitive requirements, the contextual features, the information provided, the number of steps required, and the numbers of answers. Both the similarities and differences in the mathematical tasks provided in the selected textbooks were analysed. The coding results reveal that the majority of tasks in both the Australian and Indonesian textbooks were presented in verbal and combined forms. Routine and closed tasks were still dominant in the four textbooks. More than 93% of tasks in the four textbooks had sufficient information for students to solve the problem. One of the Australian textbooks had a higher proportion of tasks with real-world contexts than the other textbooks. One of the Indonesian textbooks showed a high proportion of tasks requiring multiple steps or procedures. These results were used to explore the learning opportunities offered by the textbooks, and the possible influence on students’ performances in international assessments. Some recommendation for the refinement of the textbooks and future research are also outlined at the end of the study